Abscisic acid‐induced gene expression in the liverwort Marchantia polymorpha is mediated by evolutionarily conserved promoter elements. Issue 4 (12th October 2015) - Ghosh, Totan K.; Kaneko, Midori; Akter, Khaleda; Murai, Shuhei; Komatsu, Kenji; Ishizaki, Kimitsune; Yamato, Katsuyuki T.; Kohchi, Takayuki; Takezawa, Daisuke
Abstract: Abscisic acid (ABA) is a phytohormone widely distributed among members of the land plant lineage (Embryophyta), regulating dormancy, stomata closure and tolerance to environmental stresses. In angiosperms (Magnoliophyta), ABA‐induced gene expression is mediated by promoter elements such as the G‐box‐like ACGT‐core motifs recognized by bZIP transcription factors. In contrast, the mode of regulation by ABA of gene expression in liverworts (Marchantiophyta), representing one of the earliest diverging land plant groups, has not been elucidated. In this study, we used promoters of the liverwort Marchantia polymorpha dehydrin and the wheat Em genes fused to the β‐glucuronidase ( GUS ) reporter gene to investigate ABA‐induced gene expression in liverworts. Transient assays of cultured cells of Marchantia indicated that ACGT‐core motifs proximal to the transcription initiation site play a role in the ABA‐induced gene expression. The RY sequence recognized by B3 transcriptional regulators was also shown to be responsible for the ABA‐induced gene expression. In transgenic Marchantia plants, ABA treatment elicited an increase in GUS expression in young gemmalings, which was abolished by simultaneous disruption of the ACGT‐core and RY elements. ABA‐induced GUS expression was less obvious in mature thalli than in young gemmalings, associated with reductions in sensitivity to exogenous ABA during gametophyte growth. In contrast, lunularic acid, which had been suggested to function as an ABA‐like substance, had no effect on GUS expression. The results demonstrate the presence of ABA‐specific response mechanisms mediated by conserved cis ‐regulatory elements in liverworts, implying that the mechanisms had been acquired in the common ancestors of embryophytes.